2017
DOI: 10.1111/plb.12569
|View full text |Cite
|
Sign up to set email alerts
|

Do understorey or overstorey traits drive tree encroachment on a drained raised bog?

Abstract: One of the most important threats to peatland ecosystems is drainage, resulting in encroachment of woody species. Our main aim was to check which features - overstorey or understorey vegetation - are more important for shaping the seedling bank of pioneer trees colonising peatlands (Pinus sylvestris and Betula pubescens). We hypothesised that tree stand parameters will be more important predictors of natural regeneration density than understorey vegetation parameters, and the former will be negatively correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…All functional diversity components and CWMs used for analyses of particular invasive species studied were calculated excluding that species, to avoid circular reasoning and biased variable importance, connected with different functional traits (Thomsen et al 2016), for example, overestimated importance of seed mass CWM for Q. rubra, with its high value of this trait. Usage of functional diversity components allows conclusions about impact of plant community on the species of interest (Kurokawa et al 2010;D'Astous et al 2013;Jagodziński et al 2017;Czortek et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…All functional diversity components and CWMs used for analyses of particular invasive species studied were calculated excluding that species, to avoid circular reasoning and biased variable importance, connected with different functional traits (Thomsen et al 2016), for example, overestimated importance of seed mass CWM for Q. rubra, with its high value of this trait. Usage of functional diversity components allows conclusions about impact of plant community on the species of interest (Kurokawa et al 2010;D'Astous et al 2013;Jagodziński et al 2017;Czortek et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In each plot, we investigated only natural regeneration of P. abies within three age-height classes (Jagodziński et al 2017): seedlings (plants germinated in the current year), short saplings (plants ≥ 1 year old and < 0.5 m tall), and tall saplings (plants 0.5-1.3 m tall). Data on other woody plant species (which rarely occurred) was collected but not analyzed.…”
Section: Data Collectionmentioning
confidence: 99%
“…A similar trend was reported by Jonášová and Prach (2004), who found similar amounts of natural P. abies regeneration in both uncleared and cleared forest patches. Our previous study (Jagodziński et al 2017) on natural regeneration of pioneer species (Pinus sylvestris and Betula pubescens) Table 2 Zero-and one-inflated beta regression models of natural regeneration of Picea abies ageheight class proportions in the regeneration layer: seedlings (germinated in the current year), short saplings (≥ 1 year old, < 50 cm height), and tall saplings (50-130 cm height). AIC of final models: seedlings 245.0 (AIC 0 = 247.5), short saplings 293.3 (AIC 0 = 299.4), and tall saplings 207.4 (AIC 0 = 210.0) also revealed that seedlings differ in ecological requirements from short saplings.…”
Section: Impact Of Resource Availabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…When scaling up different leaf traits to whole ecosystems [36,37], the structural parameters of ecosystems are some of the most important controlling factors [38,39]. However, species in the same vertical stratification, such as the tree and grass layers in temperate forests and the trees, shrubs, and grasses in tropical rainforests, have similar living environments, and thus similar leaf traits [40][41][42][43][44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%